2014
DOI: 10.1186/1471-2458-14-919
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition interventions at point-of-sale to encourage healthier food purchasing: a systematic review

Abstract: BackgroundPoint-of-sale is a potentially important opportunity to promote healthy eating through nutrition education and environment modification. The aim of this review was to describe and review the evidence of effectiveness of various types of interventions that have been used at point-of-sale to encourage purchase and/or eating of healthier food and to improve health outcomes, and the extent to which effectiveness was related to intensity, duration and intervention setting.MethodsRecords from searches in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 42 publications
6
131
0
1
Order By: Relevance
“…Addressing this barrier was considered beyond the scope of the work. Social Cognitive Theory emphasizes intervening to improve both the food environment (e.g., FV access) and behavioral capacity (knowledge and skills to increase FV intake) [41,42]. As such, a multilevel approach to comprehensively address influences on farmers' market use may have improved lesson effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this barrier was considered beyond the scope of the work. Social Cognitive Theory emphasizes intervening to improve both the food environment (e.g., FV access) and behavioral capacity (knowledge and skills to increase FV intake) [41,42]. As such, a multilevel approach to comprehensively address influences on farmers' market use may have improved lesson effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, strong evidence for supermarket interventions, particularly those that provide nutrition education only at point of purchase, is somewhat lacking (8) , although interventions with a price intervention show more promise (13,45,46) . Nutrition education alone may not be adequate to drive real and sustained change to the household food supply.…”
Section: Discussionmentioning
confidence: 99%
“…BMI was categorised into three weight status groups consistent with the World Health Organization (20) cut-offs. Age was categorised into three groups consistent with those used in the latest Australian Health Survey (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and 51-70 years).…”
Section: Methodsmentioning
confidence: 99%
“…32 Other studies that examined the impact of price discounting strategies have shown promise, but are difficult to compare with our findings. 10,11 The discounts were offered via different mediums and in different populations, assessed benefits differently and offered smaller or larger discounts. This current study adds modelled fiscal strategies to the list of modelled vaccination and pharmacotherapy strategies that have been shown to be cost-effective specifically for the Aboriginal and Torres Strait Islander population, using similar economic 36 It highlights useful areas of potential future nutrition research (dietary behaviour response to fiscal strategies and/or nutrition education).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, the cost of food and the socioeconomic position of the Aboriginal and Torres Strait Islander population in remote locations are key determinants of their poor quality diet. 8,9 While there is growing evidence that fiscal measures applied to food and beverages can potentially influence consumption patterns and improve health outcomes, 10,11 most preventive interventions in Australia use nutrition information and education approaches alone where the evidence is less clear.…”
Section: N Australia Aboriginal and Torres Straitmentioning
confidence: 99%